To solve the equation \(3x - 2 = 4x + 5\), follow these steps:
-
First, let's isolate the variable \(x\). We can start by moving all terms involving \(x\) to one side and constant terms to the other side. We can do this by subtracting \(3x\) from both sides:
\[ -2 = 4x - 3x + 5 \]
This simplifies to:
\[ -2 = x + 5 \]
-
Next, subtract \(5\) from both sides to isolate \(x\):
\[ -2 - 5 = x \]
This simplifies to:
\[ -7 = x \]
-
Therefore, the solution to the equation is:
\[ x = -7 \]
You can verify the solution by substituting \(x = -7\) back into the original equation:
\[ 3(-7) - 2 = 4(-7) + 5 \] \[ -21 - 2 = -28 + 5 \] \[ -23 = -23 \]
Since both sides are equal, the solution \(x = -7\) is correct!